Molecular evidence of a Trypanosoma brucei gambiense sylvatic cycle in the human african trypanosomiasis foci of Equatorial Guinea - Cordon-Obras, Carlos; Rodriguez, Yasmin Fermin; Fernandez-Martinez, Amalia; Cano, Jorge; Ndong-Mabale, Nicolas; Ncogo-Ada, Policarpo; Ndongo-Asumu, Pedro; Aparicio, Pilar; Navarro, Miguel; Benito, Agustin; Bart, Jean-Mathieu (Frontiers in Microbiology, 2015)
Gambiense trypanosomiasis is considered an anthroponotic disease. Consequently, control programs are generally aimed at stopping transmission of Trypanosoma brucei gambiense (T. b. gambiense) by detecting and treating human cases. However, the persistence of numerous foci despite efforts to eliminate this disease questions this strategy as unique tool to pursue the eradication. The role of animals as a reservoir of T. b. gambiense is still controversial, but could partly explain maintenance of the infection at hypo-endemic levels. In the present study, we evaluated the presence of T. b. gambiense in wild animals in Equatorial Guinea. The infection rate ranged from 0.8% in the insular focus of Luba to more than 12% in Mbini, a focus with a constant trickle of human cases. The parasite was detected in a wide range of animal species including four species never described previously as putative reservoirs. Our study comes to reinforce the hypothesis that animals may play a role in the persistence of T. b. gambiense transmission, being particularly relevant in low transmission settings. Under these conditions the integration of sustained vector control and medical interventions should be considered to achieve the elimination of Gambiense trypanosomiasis.